70=0.6r

Simple and best practice solution for 70=0.6r equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 70=0.6r equation:


Simplifying
70 = 0.6r

Solving
70 = 0.6r

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '-0.6r' to each side of the equation.
70 + -0.6r = 0.6r + -0.6r

Combine like terms: 0.6r + -0.6r = 0.0
70 + -0.6r = 0.0

Add '-70' to each side of the equation.
70 + -70 + -0.6r = 0.0 + -70

Combine like terms: 70 + -70 = 0
0 + -0.6r = 0.0 + -70
-0.6r = 0.0 + -70

Combine like terms: 0.0 + -70 = -70
-0.6r = -70

Divide each side by '-0.6'.
r = 116.6666667

Simplifying
r = 116.6666667

See similar equations:

| c^2+12c+36-q^2= | | F(x)x=2.4 | | z+48=136 | | 4x^6+6x^3-7= | | x^2-9+x^2-x=180 | | 4x+12=-3x-9 | | F(x)whenx=2.4 | | -4(8-2m)=-96 | | 4a-3[a-(2a+1)]= | | 2x-85=11x+167 | | x^2-0+45=0 | | A+6a-14=64 | | w^8+17w^4+70= | | 7x+2yz=-3x+1 | | -76-34-16-34= | | 3x-7.6=29.6 | | X+2x+X=90 | | v=20+3u | | x-4forx=6 | | (x+6.5)(x-6.5)=0 | | -x^2+0+45=0 | | 5x-(-6)=46 | | X+2x+2=90 | | 3x-66=11x+134 | | 5x-(-7)=22 | | 30=(-13) | | -x^4+2x^2+35=0 | | 2(z-3)+4(2z-7)= | | 9w-17w=-16 | | 48y^2+120y+75=0 | | -65-(+42)= | | 5b+2b-6=15 |

Equations solver categories